Kenya : Fiscal Transparency Evaluation. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses key findings of the Fiscal Transparency Evaluation of Kenya. Since 2010, the Treasury has made important changes in Kenya's public financial management framework, the impact of which can clearly be seen in its performance against the Fiscal Transparency Code. The prospects for quick improvements in the fiscal reporting area are clearly within the grasp of the National Treasury. Fiscal forecasting and budgeting practices are generally in line with good practice under the Fiscal Transparency Code, reflecting more than a decade of experience with medium-term budgeting and preparing and presenting macro frameworks.